1991
DOI: 10.1111/j.1467-8624.1991.tb01568.x
|View full text |Cite
|
Sign up to set email alerts
|

Early Differentiation of Causal Mechanisms Appropriate to Biological and Nonbiological Kinds

Abstract: Although Piaget characterized young children as precausal until about 7-8 years of age, recent work indicates that preschoolers do honor fundamental principles of causality. This literature has mainly focused on general principles invoked in reasoning about mechanical events. By contrast, the present study examined whether children differentiate between the causal mechanisms appropriate for different conceptual domains. The results of 3 preliminary investigations and 1 main experiment suggested that preschoole… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
80
0
1

Year Published

2000
2000
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 86 publications
(85 citation statements)
references
References 9 publications
4
80
0
1
Order By: Relevance
“…Carey suggests that children do not develop sophisticated biological theories until the age of 9 or 10. In contrast, there is a growing number of studies showing that children do have naive biological knowledge and apply this knowledge when they are asked to classify objects as living or nonliving (Gelman et aI., 1983;Hatano & Inagaki, 1994;Springer & Keil, 1991). Thus Inagaki and Hatano (Inagaki & Hatano, 1994;Hatano, Siegler, Richards, Inagaki, Stavy, & Wax, 1993), have reported that young children hold some biological beliefs distinct from psychology.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Carey suggests that children do not develop sophisticated biological theories until the age of 9 or 10. In contrast, there is a growing number of studies showing that children do have naive biological knowledge and apply this knowledge when they are asked to classify objects as living or nonliving (Gelman et aI., 1983;Hatano & Inagaki, 1994;Springer & Keil, 1991). Thus Inagaki and Hatano (Inagaki & Hatano, 1994;Hatano, Siegler, Richards, Inagaki, Stavy, & Wax, 1993), have reported that young children hold some biological beliefs distinct from psychology.…”
Section: Introductionmentioning
confidence: 99%
“…It has been studied mainly as a concept showing the degree of cognitive development of a child (Piaget, 1929;Laurendeau & Pinard, 1962;Looft, 1974;Brown & Desforges, 1977;Lucas, Linke, & Sedgwick, 1979;Tamir, Gal-Chopin, Nussinovitz, 1981;Gelman, Spelk, & Meek, 1983;Carey, 1985;Springer & Keil, 1991;Rosengren, Gelman, Kalish, & McCormick, 1991;Backscheider, Shatz, & We would ike to thank Marianthi Sarmonika and Christina Tyrosvouti for their help in collection of the experimental data. and preparation of the teaching intervention.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite a) the indications that preschool children often invoke natural causes rather than restricting their accounts to animistic, artificialistic or teleological elements (Stepans & Kuehn, 1985;Springer & Keil, 1991;Backscheider, Shatz & Gelman, 1993), and b) the importance of explanation in the educational process, systematic empirical attempts to focus on the characteristics of preschool children's explanations on natural phenomena are limited. Taking into consideration the importance of explanation in children's scientific learning and the fact that even before entering the formal structures of education they have already developed the capability of manipulating explanations of different types involving early causal schemas (Donaldson & Elliot, 1990), this paper sets out to explore the characteristics of children's explanations of two natural phenomena: plant growth and rain formation.…”
mentioning
confidence: 97%
“…Thus, preschoolers can be proficient in causal thinking and capable of applying physical causality to familiar objects, probably directly experienced by them, such as changes concerning plants. On the other hand, even older children revert to non-naturalistic causal explanations when an event is unfamiliar, i.e., beyond their direct experience, such as cloud formation and movement (Springer & Keil, 1991).…”
mentioning
confidence: 99%